Perception Threshold of Locomotor Symmetry While Walking on a Split-Belt Treadmill in Healthy Elderly Individuals. Issue 2 (April 2014) - Lauzière, Séléna; Miéville, Carole; Duclos, Cyril; Aissaoui, Rachid; Nadeau, Sylvie
Some hemiparetic patients walk asymmetrically. To better understand the mechanisms of this deficiency, the perception of locomotor symmetry was investigated in healthy elderly individuals. 16 participants (6 women, 10 men; M age = 70.9 yr., SD = 4.1) walked on a split-belt treadmill either at a self-selected or imposed gait speed. The speed of the two belts was initially similar (or different) and then gradually differed (or matched), so participants had to detect the point of perceived asymmetry (or symmetry). The results revealed that thresholds occurred when the belt speed ratios were .88 and .85. Initial gait speed did not affect the threshold. The parameter that correlated the most with belt speed asymmetry was stance time of the parameters measured. Future studies will investigate whether stroke affects gait symmetry judgments.